Penambahbaikan pengurusan penyemakan semula senarai nilaian pihak berkuasa tempatan - Raja Abdullah, Raja Nor Wafiah (2009)
Valuation List (VL) revision is a process of revaluating all rate-able holdings under local authorities province in order to produce a new VL. VL is a complete record of information related to all rate-able holdings and need to be prepared once every five years in order to produce more equitable distribution of property tax (171 Act). Nevertheless, not all local authorities in Malaysia capable in terms of handling the revaluation exercises efficiently based on management or valuation process. The purpose of this research is to study the inability factors of local authorities’ to handle the quinquennial revaluation. Objectives of this research which are first to study the management aspects in conducting revaluation practices at local authorities, secondly to study the causing factors of hard periodic implementation in revaluation exercises, and lastly to examine the local authorities financial implication from the revaluation exercises. Data collection, questionnaire distribution, interview and theoretical study in this research were done for 19 local authorities. These local authorities are city council, town council and district council. The data collected were then analyzed using frequency analysis, descriptive analysis and Likert scale. Research result shows the constraint factors faced by local authorities are the local and state authority rating comprehension, lack of manpower, duration and cost to carry out the revaluation and taxpayers’ co-operations. Besides that, this research also explains about the positive effects whereby the implemented revaluation can increase the local authorities’ income. In the last part of this thesis, some suggestions for the problem solving were highlighted such as to increase the valuation staff, using mass valuation method and privatization. This research will help the local authorities to carry out the revaluation exercises more efficiently in the future.